2017
DOI: 10.1080/03601234.2017.1261539
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ni accumulation capability by fungi for a possible approach to remove metals from soils and waters

Abstract: Abandoned industrial sites and mines may constitute possible hazards for surrounding environment due to the presence of toxic compounds that may contaminate soils and waters. The possibility to remove metal contaminants, specifically nickel (Ni), by means of fungi was presented exploiting a set of fungal strains isolated from a Ligurian dismissed mine. The achieved results demonstrate the high Ni(II) tolerance, up to 500 mg Ni l, and removal capability of a Trichoderma harzianum strain. This latter hyperaccumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Bioaccumulation comprises the incorporation of many processes such as complexation, electrostatic attraction, covalent binding, ion exchange, van der Waals forces, precipitation, and adsorption (Vaishaly et al, 2015). Uptake of metal ions by fungi has been stated to involve an initial rapid binding of metal ions to negative functional cell wall groups, such as amide, carboxyl, phosphate, hydroxyl, and sulfhydryl followed by a slower energy-dependent entry (Cecchi et al, 2017a).…”
Section: Sem Tem and Edx Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioaccumulation comprises the incorporation of many processes such as complexation, electrostatic attraction, covalent binding, ion exchange, van der Waals forces, precipitation, and adsorption (Vaishaly et al, 2015). Uptake of metal ions by fungi has been stated to involve an initial rapid binding of metal ions to negative functional cell wall groups, such as amide, carboxyl, phosphate, hydroxyl, and sulfhydryl followed by a slower energy-dependent entry (Cecchi et al, 2017a).…”
Section: Sem Tem and Edx Investigationsmentioning
confidence: 99%
“…Fungal cell wall is the primary interaction site with the metal, composed of chitin, chitosan, glucan, polysaccharides, lipids and proteins with enormous functional groups (hydroxyl, carboxylate, sulfate, phosphate, and amino) ( Abbas et al., 2014 ). Several fungal species were reported to be involved in detoxification of various metals contaminants, for example, removal of V(II) by Aspergillus terreus , Cladosporium cladosporioides , Paecilomyces lilacinus , Penicillium citrinum and Rhizopus arrhizus ( Ceci et al., 2012 ), Cu(II) by Trichoderma viride ( Wang and Wang, 2013 ), Ni(II) by T. harzianum ( Cecchi et al., 2017a ), Ag(I) by A. alliaceus , T. harzianum , and Clonostachys rosea ( Cecchi et al., 2017b ), Pb(II) by different Pleurotus sp ( Dulay et al., 2015 ), Zn(II) by P. janthinellum , P. olsonii and P. waksmanii ( Di Piazza et al., 2018 ), Cd(II) by A. versicolor ( Fazli et al., 2015 ), Fe(III), Mn(II), Cu(II), Zn(II), and Pb(II) by Mucor circinelloides ( Zhang et al., 2017 ) were studied.…”
Section: Introductionmentioning
confidence: 99%
“…The genus has been reported to accumulate high levels of PTEs and is used for mycoremediation of copper (Kapahi and Sachdeva 2017;Vaseem et al 2017). Interestingly, some native microfungal strains (Aspergillus, Trichoderma harzianum, Clonostachys rosea) have been isolated from a silver-polluted site indicating silver myco-accumulation from metal contaminated wasterock dump sites (Cecchi et al 2017). Another example is the assessment of Ni accumulation by fungi for a possible approach to remove metals from soil and water (Cecchi et al 2017).…”
Section: Importance Of Bioremediationmentioning
confidence: 99%
“…The ability of fungi to take up elements makes them useful soil quality indicators as well as potential bioremediation agents for substrata contaminated with toxic elements such as heavy metals, metalloids, and radionuclides [11][12][13][14][15][16]. For instance, some authors [17] have observed that the macrofungal species Agaricus macrosporus Mont.…”
Section: Introductionmentioning
confidence: 99%